2000
DOI: 10.1126/science.290.5494.1159
|View full text |Cite
|
Sign up to set email alerts
|

Transgene and Transposon Silencing in Chlamydomonas reinhardtii by a DEAH-Box RNA Helicase

Abstract: The molecular mechanism(s) responsible for posttranscriptional gene silencing and RNA interference remain poorly understood. We have cloned a gene ( Mut6 ) from the unicellular green alga Chlamydomonas reinhardtii that is required for the silencing of a transgene and two transposon families. Mut6 encodes a protein that is highly homologous to RNA helicases of the DEAH-box family. This protein is necessary for the degradation of certain abe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
156
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(160 citation statements)
references
References 29 publications
2
156
0
2
Order By: Relevance
“…Therefore, it is conceivable that a cell devoting much of its RNAi machinery to the process of mRNA degradation could become defective in chromosome function or be more susceptible to viral infection. Finally, worms and green algae with defects in the RNAi machinery have a higher incidence of transposon hopping, which in turn could lead to increased mutagenesis (21)(22)(23). It is unknown whether this function is conserved in humans, but, if so, siRNA could lead to genome instability and cancer later in life.…”
Section: Figmentioning
confidence: 99%
“…Therefore, it is conceivable that a cell devoting much of its RNAi machinery to the process of mRNA degradation could become defective in chromosome function or be more susceptible to viral infection. Finally, worms and green algae with defects in the RNAi machinery have a higher incidence of transposon hopping, which in turn could lead to increased mutagenesis (21)(22)(23). It is unknown whether this function is conserved in humans, but, if so, siRNA could lead to genome instability and cancer later in life.…”
Section: Figmentioning
confidence: 99%
“…The helicase plays important roles in cell proliferation and organ maturation (Iggo et al 1991;Stevenson et al 1998) and belongs to a large family of highly evolutionarily conserved proteins, the so-called DEAD-box family of putative ATPases and helicases (for review, see de la Cruz et al 1999). Recent studies have revealed several RNA helicases including mut6 (Wu-Scharf et al 2000), SDE3 (Dalmay et al 2001), mut14 (Tijsterman et al 2002), drh-1 (Tabara et al 2002), and spindle-E (Kennerdell et al 2002) required for RNAi and related posttranscriptional gene silencing (PTGS) pathways. Dmp68 is similar to, but clearly not an ortholog of these proteins.…”
Section: Genes and Development 2503mentioning
confidence: 99%
“…Antisense constructs probably also produce RNAs that feed into the dsRNA-induced degradation pathway [38], [39]. A DEAH-box RNA helicase (Mut6) that is involved in degrading misspliced and nonpolyadenylated transcript was shown to be required for transgene and transposon silencing in the unicellular green alga Chlamydomonas reinhardtii [33]. These results suggest a partial overlapbetween NMD and PTGS pathways and provide new insights for unraveling the PTGS pathway.…”
Section: Cellular Protein Involved In Posttranscriptional Gene Silencingmentioning
confidence: 88%
“…The obligatory nuclear localization of the cucumber mosaic virus 2b protein [32] should help to identify steps of PTGS that occur in the nucleus. The host defense function of RNA-mediated silencing is demonstrated by the inc r e a s e d o f s e n s i t i v i t y o f Arabidopsis PTGS mutants to some viruses [21] and the mobilization of transposons in the Mut6 mutant Chlamydomonas [33]. Apart from an enhanced susceptibility to viral infection, Arabidopsis sgs/sde mutants appear normal [21].…”
Section: Viral Suppressors Of Posttranscriptional Gene Silencingmentioning
confidence: 99%
See 1 more Smart Citation